Effects of processing parameters on the yield of cellulose isolated from banana leaves - Pavithra, Murukhaiya (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Cellulose is widely used in many aspect and industries such as food industry, pharmaceutical, paint, polymers and many more. In this project, cellulose were isolated from banana leaves and the effects of processing parameters such as effects of temperature, reaction time and acid concentration on the yield of cellulose isolated from banana leaves were determined. Banana leaves were treated with acidified sodium chlorite (NaClO;) and sodium hydroxide (NaOH) to remove lignin and hemicelluloses respectively. Treatment of sample with 4% wt. of NaClO, and NaOH for 2 hours at 70 "C is the optimum condition for the highest yield of cellulose which is 28.3%. The obtained chemically-purified cellulose fibers were dissoluted in NTU solution and cellulose nanoparticles were synthesised by using various concentrations such as 0.01 %, 0.03%, 0.05%, 0.07% and 0.1 %. As concentration of cellulose solution increase, particle size increase together from 142 ± 31 nm to 271 ± 76 nm. The obtained pure cellulose and cellulose nanoparticles were investigated by using SEM and FTIR.